Pelatihan Transparansi dan Akuntabilitas di Yayasan Radiyatan Mardiyah Prumpung Jakarta Timur - Lucyanda, Jurica; Iman Santoso, Berkah; Hady, Shofiyah; Permana, Fadil; Widiastuti, Tuti (LPkM Universitas Bakrie, 2023)
The community service aims to provide training and assistance related to the transparency and accountability of the foundation from law, communication, accounting, and information technology at the Radiyatan Mardiyah Foundation (YRM) Prumpung East Jakarta. Currently, YRM is facing several problems, that is does not have a deed of establishment of the foundation. In addition, YRM's financial statements are still simple and have not made financial statements based on the Foundation's financial accounting standards (Interpretation of Financial Accounting Standards/ISAK 35). This problem is due to the limited understanding of the foundation management related to the transparency and accountability of the foundation. These limitations are important to be facilitated by providing training and assistance related to transparency from the perspective of law, communication, accounting, and information technology. This activity builds a YRM web and financial report application based on information technology based ISAK 35. The foundation's transparency and accountability training from law, communication, accounting, and informatics techniques was felt by participants to provide additional knowledge and understanding related to the foundation's transparency and accountability. Participants were satisfied with the material provided because it was in accordance with the information needs that were needed by the foundation management. This activity provides benefits for trainees on how important transparency and accountability are for the foundation. The output of this service is that YRM immediately has a legal entity and is able to implement the information technology-based financial statements based on ISAK 35.